PENGARUH ATRIBUT PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE SAMSUNG ANDROID DI KABUPATEN GIANYAR - Darmayanti, Ni Ketut; Jatra, I Made (E-Jurnal Manajemen, 2015)
The purpose of this study was to determine the effect of product attributes and brand image on the Samsung Android Smartphone on purchasing decisions in Gianyar regency. Research conducted on respondents who never make purchasing decisions and using Samsung Android Smartphone in Gianyar and the number of samples set at 104 respondents using purposive sampling technique. To find out how far the product attributes and brand image influence the purchasing decisions of consumers use multiple linear regression analysis techniques. The results showed that the variable product attributes and brand image has a positive and significant influence on consumer purchasing decisions.
Keywords: atribut produk; citra merek; keputusan pembelian konsumen